Estado e políticas de gestão pública: uma análise garantista em municípios do noroeste Rio-Grandense - Severo, Rodrigo (2017)
In a context in which Public Administration suffers from a lack of proficiency and probity, governments need management policies that may renew it. This dissertation is the result of a research belonging to the juridical-theoretical aspect. The qualitative methodology used, and the motivation, for exploratory purposes, is to improve the proficiency of Public Administration through Public Management Policies. The objective of the study was to map, analyze and understand, from a guarantor point of view, the Public Management Policies. Initially, through a bibliographical research, a historical, conceptual and legal study of the State and Public Administration was carried out. Next, a theoretical framework was built based on doctrine and law, which allowed us to understand what these policies are. In order to provide factual support, a telematic-documentary research was selected in the scope of the Public Administration of the executive power in four municipalities of the meso-region Noroeste Rio-grandense – Erechim, Ijuí, Santo Ângelo and Santa Rosa – the instruments of budgetary planning and management – PPA, LDO and LOA. In analytical terms, with the purpose of recognizing the visibility and the protagonism of these policies, its priorities and trends were mapped in four domains (areas) - "Role of the State, organizational architecture and administrative services"; "Tax adjustment, collection and control"; "Quality and transparency in the provision of public services"; and "Human resource policies" – besides to identifying the alignment between the instruments. The literature confirmed the visibility and necessity of its protagonism, emphasizing that the Public Administration should be thought from a conception of Public Policy, based on the subordination to the constitutional precepts. The phatic support made it possible to confirm the alignment between the instruments and the role of Public Management Policies, prioritizing those of "Human Resources", among 167 interventions in the four domains. The study showed that most municipal governments have been concerned with guiding and planning the directions of their Administrations through Public Management Policies, as well as executing them for administrative proficiency, and ensuring good governance and good administration. In this way, the protagonism and constant improvement of the Public Management Policies become of fundamental importance to minimize problems consequent from the lack of proficiency and probity of the Public Administration.